Metabolic Encephalopathy and Lipid Storage Myopathy Associated with a Presumptive Mitochondrial Fatty Acid Oxidation Defect in a Dog - Biegen, Vanessa R.; McCue, John P.; Donovan, Taryn A.; Shelton, G. Diane (Frontiers in Veterinary Science, 2015)
A 1-year-old spayed female Shih Tzu presented for episodic abnormalities of posture and mentation. Neurologic examination was consistent with a bilaterally symmetric multifocal encephalopathy. The dog had a waxing-and-waning hyperlactemia and hypoglycemia. Magnetic resonance imaging revealed bilaterally symmetric cavitated lesions of the caudate nuclei with less severe abnormalities in the cerebellar nuclei. Empirical therapy was unsuccessful and the patient was euthanized. Post-mortem histopathology revealed bilaterally symmetric necrotic lesions of the caudate and cerebellar nuclei and multi-organ lipid accumulation, including a lipid storage myopathy. Malonic aciduria and ketonuria were found on urinary organic acid screen. Plasma acylcarnitine analysis suggested a fatty acid oxidation defect. Fatty acid oxidation disorders are inborn errors of metabolism documented in humans, but poorly described in dogs. Although neurologic signs have been described in humans with this group of diseases, descriptions of advanced imaging and histopathology are severely lacking. This report suggests that abnormalities of fatty acid metabolism may cause severe, bilateral gray matter necrosis and lipid accumulation in multiple organs including the skeletal muscles, liver, and kidneys. Veterinarians should be aware that fatty acid oxidation disorders, although potentially fatal, may be treatable. A timely definitive diagnosis is essential in guiding therapy.